Rancang Bangun Aplikasi Rental Sepeda Motor Berbasis Mobile dengan Metode Waterfall untuk Efesiensi dan Kualitas Optimal - Muhammad Rizqi Retrianto; Anita Fira Waluyo (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to develop a mobile-based motorbike rental application using the programming language PHP, Kotlin, and REST API with the problems identified in this research being the process of ordering and managing rental motorbike data which is still manual and less efficient, as well as knowing the selection of motorbikes and When renting you have to come directly to the place. The impact of this problem is increased operational costs and lack of customer satisfaction. The method used in this research is system development design, with a focus on analysis, design, implementation and application testing. The result of this research is a motorbike rental application that can be used by users to order motorbikes online and make payments for rented motorbikes. The back-end of this application was created using the PHP programming language, Kotlin for mobile application development, and uses the REST API as a bridge between the back-end and front-end. In conclusion, the mobile-based motorbike rental application developed in this research can help as a solution to increase efficiency and security in the ordering process and managing motorbike rental data.